WOX9 functions antagonistic to STF and LAM1 to regulate leaf blade expansion in Medicago truncatula and Nicotiana sylvestris. Issue 3 (20th October 2020) - Wolabu, Tezera W.; Wang, Hui; Tadesse, Dimiru; Zhang, Fei; Behzadirad, Marjan; Tvorogova, Varvara E.; Abdelmageed, Haggag; Liu, Ye; Chen, Naichong; Chen, Jianghua; Allen, Randy D.; Tadege, Million
Summary: WOX family transcription factors regulate multiple developmental programs. The intermediate clade transcriptional activator WOX9 functions together with the modern clade transcriptional repressor WOX genes in embryogenesis and meristems maintenance, but the mechanism of this interaction is unclear. STF and LAM1 are WOX1 orthologs required for leaf blade outgrowth in Medicago truncatula and Nicotiana sylvestris, respectively. Using biochemical methods and genome editing technology, here we show that WOX9 is an abaxial factor and functions antagonistically to STF and LAM1 to regulate leaf blade development. While NsWOX9 ectopic expression enhances the lam1 mutant phenotype, and antisense expression partially rescues the lam1 mutant, both overexpression and knockout of NsWOX9 in N. sylvestris resulted in a range of severe leaf blade distortions, indicating important role in blade development. Our results indicate that direct repression of WOX9 by WUS clade repressor STF/LAM1 is required for correct blade architecture and patterning in M. truncatula and N. sylvestris . These findings suggest that controlling transcriptional activation and repression mechanisms by direct interaction of activator and repressor WOX genes may be required for cell proliferation and differentiation homeostasis, and could be an evolutionarily conserved mechanism for the development of complex and diverse morphology in flowering plants.